THE EFFECT OF THE PERCEPTION AND TRUST OF MSME ACTIVITIES IN NGALIYAN REGENCY, SEMARANG IN USING SHARIA BANKING FINANCING SERVICES - Nida Indika Deswara (Jurnal Ilmiah Ekonomi Islam, 2023)
The objective of this study was to determine the influence of perceptions and trust as a driving factor for MSMEs to choose to use Islamic banking financing products and to determine why MSME actors still do not choose and use Islamic financing. This study uses multiple regression analysis and data collection techniques using surveys by distributing questionnaires to the participants. A total of 87 MSME actors in Ngaliyan Subdistrict Semarang were selected as research objects using a random sampling technique. The analysis test results show that the perception and trust variables do not significantly increase the influence of MSMEs in the decision to choose sharia financing services.